Níveis de metionina + cistina para codornas japonesas em fase de postura submetidas a diferentes ambientes térmicos - Souza, Rannyelle Gomes (2019)
Coturniculture in Basil has been consolidated as a profitable activity, which presents characteristics such as small space requirement, low feed intake, small generation interval, early sexual maturity, rusticity and high initial growth rate. Considering that Brazil is located south of the line of Ecuador, in the hottest part of the globe especially in summer, it is understood that priority should be given to problems related to heat stress. The objective of this work was to evaluate if the Methionine + Cystine minimizes the deleterious effects of heat stress on the production and egg quality of laying quails. The study was conducted in the city of Areia / PB and a total of 504 Japanese quail (Coturnix coturnix japonica) was used in the production phase at 54 days of life. The animals were distributed in cages, according to a completely randomized 3x4 factorial design, with three levels of methionine + cystine (NRC 100%, 110% and 120%) and four temperature ranges (20, 24, 28 and 32 ° C) representing thermoneutrality and thermal stress ranges, totaling twelve treatments with six replicates of seven birds each, totaling 72 plots. The performance characteristics evaluated in the experimental trial were: feed intake, laying percentage, egg percentage egg mass, feed conversion per dozen and mass of eggs produced. The quality characteristics evaluated were: specific gravity, percentages of yolk, albumen and bark, bark thickness, eggshell weight and Haugh unit and yolk color. It was not observed (p> 0.05) in the interaction of the methionine + cystine factors and temperature ranges on the variables related to performance and egg quality. The temperature of the climatic steers influenced egg performance and egg quality, as the egg temperature was increased, the results were worse, except for the yolk color, which was not influenced by the temperature treatment. Thus, for Japanese laying quails, a temperature range between 20 and 28 ° C is indicated, since in this range both performance and egg quality parameters were not affected. It is recommended to use the lowest level (100%) of DL-methionine + cystine, making it more economically viable to the producer, since the supplementation of Methionine + Cystine did not reverse the deleterious effects of thermal stress in the production and quality eggs.